2017
DOI: 10.1063/1.4994396
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of the positron-acoustic waves in electron-positron-ion plasmas with κ deformed Kaniadakis distributed electrons and hot positrons

Abstract: Qualitative analysis of the positron acoustic (PA) waves in a four-component plasma system consisting of static positive ions, mobile cold positron, and Kaniadakis distributed hot positrons and electrons is investigated. Using the reductive perturbation technique, the Korteweg-de Vries (K-dV) equation and the modified KdV equation are derived for the PA waves. Variations of the total energy of the conservative systems corresponding to the KdV and mKdV equations are presented. Applying numerical computations, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Thus, the compressive and rarefactive DIASWs abate as κ is increased, i.e., the compressive and rarefactive DIASWs shrink as the electrons evolve far away from its Maxwell-Boltzmann equilibrium. It is important to note that the value of κ has no effect on the DIASWs associated with the KdV equation (23), whereas the values of κ have a significant effect on DIASWs linked with the mKdV equation (33).…”
Section: Derivation Of Mkdv Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the compressive and rarefactive DIASWs abate as κ is increased, i.e., the compressive and rarefactive DIASWs shrink as the electrons evolve far away from its Maxwell-Boltzmann equilibrium. It is important to note that the value of κ has no effect on the DIASWs associated with the KdV equation (23), whereas the values of κ have a significant effect on DIASWs linked with the mKdV equation (33).…”
Section: Derivation Of Mkdv Equationmentioning
confidence: 99%
“…They showed that the κ-deformed parameter very slightly changes the structural properties of IASWs [32]. The qualitative analysis of the positron acoustic waves in four-component plasma in which electron and hot positron obey κ-deformed distribution has been carried by Saha and Tamang [33]. The use of κ-deformed Kaniadakis distribution in the context of arbitrary amplitude IASWs in a magnetized plasma (composed of cold fluid ions and non-Maxwellian electrons), where the electrons obey the κdeformed Kaniadakis distribution, was made very recently in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it has attracted the interest of many researchers over the last 16 years, who have studied its foundations and mathematical aspects [5][6][7][8][9][10][11][12], the underlying thermodynamics [13][14][15][16][17], and specific applications of the theory in various scientific and engineering fields. A non-exhaustive list of application areas includes quantum statistics [18][19][20], quantum entanglement [21,22], plasma physics [23][24][25][26][27], nuclear fission [28], astrophysics [29][30][31][32][33][34][35], geomechanics [36], genomics [37], complex networks [38,39], economy [40][41][42][43] and finance [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it has attracted the interest of many researchers over the last two decades who have studied its foundations and mathematical aspects [49][50][51][52][53][54][55][56][57][58] , the underlying thermodynamics 59,60 , and specific applications of the theory to various fields. A non-exhaustive list of applications includes those in quantum statistics [61][62][63][64] , in quantum entanglement 65,66 , in plasma physics [67][68][69][70][71][72][73] , in nuclear fission [74][75][76][77] , in astrophysics [78][79][80][81] , in quantum gravity [82][83][84][85][86][87] , in geomechanics 88,89 , in genomics 90,91 , in complex networks [92][93][94] , in economy [95]…”
mentioning
confidence: 99%